2022
DOI: 10.1007/s12671-022-01899-3
|View full text |Cite
|
Sign up to set email alerts
|

Meditators’ Non-academic Definition of Mindfulness

Abstract: Objectives Mindfulness has been defined differently in academic scientific contexts and in Buddhist academic contexts. An under-studied area is that of lay (non-academic) theories of mindfulness. The goal of this article is to identify, organize, analyze in detail, and provide themes from the meditators’ definitions of mindfulness. Possible differences and similarities of the collected definitions of mindfulness with the scientific-academic definitions and with the academic-Buddhist definitions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…As we navigate through the different domains in our lives, our capacity of awareness here and now with curiosity and without any judgment as to what we experience (Alvear et al, 2022), can allow the creation of mindful spaces. In this respect, mindful experiential learning can offer a skillful means for cultivating inclusivity both internally (within our minds) and externally (as we design spaces).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we navigate through the different domains in our lives, our capacity of awareness here and now with curiosity and without any judgment as to what we experience (Alvear et al, 2022), can allow the creation of mindful spaces. In this respect, mindful experiential learning can offer a skillful means for cultivating inclusivity both internally (within our minds) and externally (as we design spaces).…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous suggestions for the definition of mindfulness across disciplinary fields (Alvear et al, 2022). To define mindfulness, Gethin (2011) reminds us of the original translation of the Buddhist term sati , which “plays on aspects of remembering, recalling, reminding, and presence of mind” (p. 275).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth stating up front that the term 'mindfulness,' although very much in vogue in science and popular culture, eludes any concrete definition. There are indeed several ongoing scholarly debates, that are all attempting to address what this term really means in the context of meditation (Alvear et al, 2022;Anālayo, 2019;Chiesa, 2013;Gethin, 2011;Nilsson & Kazemi, 2016). The confusion here is not totally unwarranted, as there are many ways one can appropriately use the term 'mindfulness': it can refer to the awareness of certain thoughts, feelings, or objects in one's experience (being mindful 'of' something); it can be used to denote a certain open attitude, or accepting posture towards aspects of one's experience (mindfulness 'as acceptance'); it can refer to a specific feeling, or a collection of feelings, e.g.…”
Section: What Is Meditation?mentioning
confidence: 99%
“…Although there have been studies that show mindfulness and impulsivity to be generally negatively correlated (Lattimore et al, 2011;Murphy & MacKillop, 2012;Peters et al, 2011;Rajesh et al, 2013), few studies have reported positive correlations between them (Lu & Huffman, 2017;Vinci et al, 2016;Wittmann et al, 2015). These inconclusive findings emphasize the difficulties of operationalizing both mindfulness (Alvear et al, 2022;Bergomi et al, 2013;Somaraju et al, 2023) and impulsivity and the necessity to examine the relationship between them from a multidimensional point of view and to qualify the findings according to the specific components being measured (Peters et al, 2011). This would broaden and deepen an examination of the relationship between these traits, which can vary at the subcomponent level.…”
mentioning
confidence: 96%